Alternative Indias : writing, nation and communalism - Morey, Peter; Tickell, Alex (Cross/cultures, 2005)
The debate over whether religious or secular identities provide the most viable model for a wider national identity has been a continuous feature of Indian politics from the late nineteenth century to the present day. Moreover, in the last thirty years the increasingly communal articulation of popular politics and the gradual rise of a constellation of Hindu nationalist parties headed by the BJP has increased the urgency of this debate. While Indian writing in English has fostered a long tradition of political dissent, and has repeatedly questioned ethnocentric, culturally exclusive forms of p.